DICTION OF SASAK STUDENT INTERACTIONS IN ISLAMIC BOARDING SCHOOL - Sudali, Ahmad (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2021)
The purpose of this study was to determine the use of Sasak students in communication at the Darul Falah IIICukir-Jombang Roudlotul Qura'an Islamic Boarding School and in areas around Tebuireng. This study uses a qualitativeresearch approach. The data obtained are in the form of oral data and data or image recordings that are carried outwhen the objects interacting about the use of Indonesian by Sasak students in both official and casual forums. Theresults of the research will be described or written in the form of a report, the data that has been collected will becollected, analyzed, described and will be removed as best as possible to answer the problem formulation in order toachieve all the objectives in this study properly. The result of the research is that the diction contained is diction relatedto meaning, namely diction based on denotative, and diction based on connotative meaning.